2014
DOI: 10.1016/j.fgb.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Wood and humus decay strategies by white-rot basidiomycetes correlate with two different dye decolorization and enzyme secretion patterns on agar plates

Abstract: During several forays for ligninolytic fungi in different Spanish native forests, 35 white-rot basidiomycetes growing on dead wood (16 species from 12 genera) and leaf litter (19 species from 10 genera) were selected for their ability to decolorize two recalcitrant aromatic dyes (Reactive Blue 38 and Reactive Black 5) added to malt extract agar medium. In this study, two dye decolorization patterns were observed and correlated with two ecophysiological groups (wood and humus white-rot basidiomycetes) and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
2
13
0
8
Order By: Relevance
“…However, the present study showed the presence of peroxidase activity. Such different peroxidase enzyme secretion patterns have been observed in white rot wood fungi and white rot humus fungi [16]. Tuber maculatum showed the presence of cellulase and laccase activities belonging to the lignocellulolytic group of enzymes as well as xylanase activity.…”
Section: Resultsmentioning
confidence: 70%
“…However, the present study showed the presence of peroxidase activity. Such different peroxidase enzyme secretion patterns have been observed in white rot wood fungi and white rot humus fungi [16]. Tuber maculatum showed the presence of cellulase and laccase activities belonging to the lignocellulolytic group of enzymes as well as xylanase activity.…”
Section: Resultsmentioning
confidence: 70%
“…In this present study, it was not possible to quantify the percentage of degradation of the dye in the solid medium, although discoloration of the culture medium was observed with isolates DF39, EF58, FUS, and PS, indicating the degradation of the dye. Barrasa et al (2014) observed that there are two patterns of discoloration of synthetic dyes in solid culture medium. According to these authors, saprophytic white rot fungi, belonging to the order Agaricales, form a brown halo external to the colony due to the increases synthesis of peroxidase enzymes and laccases on the colony edges.…”
Section: Mycelial Growth and Discoloration Of Methylene Blue In The Smentioning
confidence: 99%
“…synthesize specific enzymes on the culture medium (Barrasa et al, 2014;Kanagaraj;Senthilvelan;Panda, 2015). For the P. ostreatus EF60 isolate, the increase in the methylene blue concentration reduced the mycelial diameter at 50 mg L -1 by 38.5%, and the mycelial growth was adjusted to a quadratic regression model.…”
Section: Mycelial Growth and Discoloration Of Methylene Blue In The Smentioning
confidence: 99%
See 1 more Smart Citation
“…Diferentes estudios muestran la capacidad que tienen los hongos de la pudrición blanca de la madera debido a que poseen un sistema oxidativo que exhibe un alto grado de especificidad, permitiéndoles degradar un amplio número de compuestos recalcitrantes además de la lignina (Anastasi et al, 2010;Barrasa et al, 2014). Actualmente se utilizan sistemas aerobios y anaerobios, con hongos y bacterias para la decoloración y mineralización de los colorantes presentes en dichas aguas (Kumar et al, 2016;Senthilkumar, Perumalsamy y Prabhu, 2014).…”
Section: Introductionunclassified